(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
The field experiment was carried out during rabi season of 1999-2000 to 2000-2001 with five recommended potato varieties viz. Heera, Dhera, Diamant, Chamak and Cardinal along with two types of mulching materials viz rice straw and water hyacinth to find out suitable variety (ies) and mulching material(s) for obtaining higher yield under no tillage condition. Heera produced highest yield under both rice straw (19.45 t/ha) and water hyacinth (23.15 t/ha) mulch. Rest of the variety performed more or less similar in both cases. Both Heera and Dhera seemed to be suitable for cultivation in no tillage condition. Key Words: Potato varieties, Mulching material, Yield and Quality. doi: 10.3329/bjsir.v44i1.2713 Bangladesh J. Sci. Ind. Res. 44(1), 51-56, 2009